(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Translation technology has advanced rapidly in recent years with the development of neural machine translation, computer-assisted translation tools, and cloud-based platforms for managing translation workflows. This article reviews the latest innovations in translation technology and analyzes their impact on the translation industry. Methods include a comprehensive literature review of research papers and industry reports. The analysis shows that while machine translation quality has improved significantly, human translators are still essential for producing high-quality translations. The article concludes with recommendations for effectively integrating innovative technologies into translation workflows.